ESTIMASI SEBARAN HIDROKARBON DENGAN MENGGUNAKAN INDIKATOR P-WAVE DIFFERENCE DISPERSION FACTOR PADA LAPANGAN BONAPARTE - Mokhammad Puput Erlangga; Handoyo Handoyo; Egie Wijaksono (Engineering Faculty Universitas Lampung, 2019)
In the hydrocarbon exploration, we need the method that result the direct hydrocarbon indicator to estimate the reservoir location and dimension accurately. It is a difficult and long standing problem. The method that used before was inverting the linearized of Zoepprit’s equation. But this method would not result the physical property depend on frequency. We know that the seismic wave propagate in the porous and fluid saturated media will attenuate and wave dispersion. This phenomenon is caused by the dissipation of seismic energy that depend on frequency. So by this idea, we will use the frequency-dependent of physical property to improve the accuracy of direct hydrocarbon indicator. The physical property will be used here is the P-Wave velocity. The method is call the P-Wave Difference Dispersion Factor (PPDF).